The impact of fitness involvement on quality of life among Taiwanese university students: Health-promoting lifestyle as a mediator - Chiu, Chung-En; Chan, Chun-Chen (International Journal of Innovative Research and Scientific Studies, 2025)
In recent years, economic growth and technological advancements have contributed to the flourishing of fitness activities in Taiwan, making them an integral aspect of young people's daily routines. This study explored whether participation in fitness activities among Taiwanese university students positively influences health-promoting lifestyle (HPL) and quality of life (QOL). This study employed a cross-sectional survey of 625 Taiwanese university students. Structural equation modeling was used to examine the relationships between fitness involvement (FI), HPL, and QOL, as well as the mediating role of HPL between FI and QOL. The findings indicate that FI is positively associated with both QOL and HPL. Furthermore, HPL is positively related to QOL and partially mediates the relationship between FI and QOL. University students' involvement in fitness not only directly enhances their QOL, but also improves their satisfaction with QOL through HPL. This finding has significant implications for educational institutions in promoting the development of campus fitness facilities and offering fitness-related courses.